High school human capital portfolio and college outcomes - Guy Tchuente (University of Kent, School of Economics, 2015)
This paper assesses the relationship between courses taken in high school and college major choice. Using High School and Beyond survey data, I study the empirical relationship between college performance and different types of courses taken during high school. I find that students sort into college majors according to subjects in which they acquired more skills in high school. However, I find a U-shaped relationship between the diversification of high school courses a student takes and their college performance. The underlying relation linking high school to college is assessed by estimating a structural model of high school human capital acquisition and college major choice. Policy experiments suggest that taking an additional quantitative course in high school increases the probability that a college student chooses a science, technology, engineering, or math major by four percentage points.
Keywords: J24; I21; 330; human capital; discrete choice; college major